Awake extracorporeal membrane oxygenation in immunosuppressed patients with severe respiratory failure—a stretch too far? - Shekar, Kiran; Abrams, Darryl; Schmidt, Matthieu (Journal of Thoracic Disease, 2019)
The use of rescue extracorporeal membrane oxygenation (ECMO) in immunocompromised patients with acute respiratory distress syndrome (ARDS) is increasing with 5% to 31% of patients receiving ECMO (1,2) in recent studies. In the recently published ECMO to Rescue Lung Injury in Severe ARDS (EOLIA) trial, 22% of the recruits were identified as immunosuppressed and the sixty-day mortality of this sub-population was 56% and 78% in the ECMO and the control groups, respectively (3). Even though a post-hoc analysis of this small subgroup may not be definitive evidence for or against ECMO use in this population, it is important to note that “salvage” VV-ECMO (4) in the immunosuppressed is a futile exercise. However, this raises two important questions beyond crude mortality of this population: (I) might this population benefit from early VV-ECMO to liberate them from invasive mechanical ventilation (IMV) as soon as feasible? and (II) can IMV be avoided altogether in this cohort?